The Effect of Non-Physical Work Environment and Work Stress on Employees’ Performance at Bank BNI Jailolo Unit, West Halmahera - Glorian Stevani Hallo; Caecilia Tri Wahyanti (International Journal of Social Science and Business, 2022)
Performance is an increase of results achieved by employees in terms of quality or quantity with the existing working hours. Employees’ performance must be considered to determine the company's existence to ensure the company's profitability. The factors that cause employees’ performance to decline are the non-physical work environment and work stress which the company still does not pay attention to. This study aims to examine the effect of non-physical work environment and work stress on employees’ performance partially and simultaneously at Bank BNI Jailolo Unit, West Halmahera. This research was conducted at Bank BNI Jailolo Unit which has 40 people including a leader and employees. Data were collected by distributing questionnaires directly to employees of Bank BNI Jailolo Unit. The results of the study show that a non-physical work environment affects the employee’s performance but work stress does not affect the employee’s performance. However, simultaneously non-physical work environment and stress affect employee performance. This is because the work environment is good enough to help employees cope with work stress and can improve the employees’ performance.